Improving exploitation of chicken manure via two-stage anaerobic digestion with an intermediate membrane contactor to extract ammonia. (November 2018) - Wang, Xuemei; Gabauer, Wolfgang; Li, Zifu; Ortner, Markus; Fuchs, Werner
Highlights: A modified process for reducing ammonia inhibition of chicken manure is addressed. Ammonia was rapidly released in the pre-hydrolysis process within the first 3–5 days. The released ammonia was removed through membrane contactor efficiently. BMP tests verified the process reduced inhibitory effects and enhanced methane yield. The proposed process effectively improves the utilization of chicken manure. Abstract: This study describes a modified process of ammonia release through pre-hydrolysis – ammonia removal via membrane contactor – methanization for counteracting ammonia inhibition in anaerobic digestion of chicken manure. In the pre-hydrolysis step, ammonia was rapidly released within the first 3–5 days. 78%-83% of the total nitrogen was finally converted into total ammonia/ammonium (TAN) with volatile fatty acids concentration of approximately 300 g/kg·VS. In the ammonia removal process, diluting the hydrolyzed chicken manure to 1:2, the TAN could be reduced to 2 g/kg in 21 h when pH was increased to 9. The final BMP test of chicken manure verified that lower TAN concentration (decreased to 2 g/kg) significantly reduced inhibitory effects, obtaining a high methane yield of 437.0 mL/g·VS. The investigations underlined several advantages of this modified process.